(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
During a space mission, the supply of the satellite with required electrical power depends on each phase of the orbit/season until its end of life. To maintain the mission, different strategies to manage the electrical power (production, storage, and distribution) could be adapted to the mission function (e.g., low earth orbit, LEO, Geosynchronous). The management strategy for the battery modules must be carried out at the head of the satellite project phases, closely with the mission definition. In our case, we propose a strategy that covers the need for a Small Geostationary Satellite (SGEO) by dimensioning its battery modules and their management system (BMS). The small GEO-SAT presents a new attractive performance for several commercial telecommunication missions, and different space agencies are interested in developing this kind of Small-TELECOM platform. This paper summarizes the power-budget analysis of a small GEO-SAT, gives results of sizing the battery module (Li-ion cells assembled), and proposes different manufacturers that could cover this kind of mission. Moreover, different battery management modes are discussed and simulated by STK and Simulink software.